PENERAPAN SISTEM INFORMASI PEMBELAJARAN ONLINE DI SMK AL-HUDA LAMPUNG SELATAN - Arif Munandar; Heni Sulistiani; Qadli Jafar Adrian; Agus Irawan (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2020)
The teaching and learning process needs to be done well and directed. Good quality of learning will certainly produce good learning outcomes. The learning process at SMK Al-Huda, South Lampung is still done through face-to-face. For this reason, Al-Huda Vocational School needs to develop an online learning system to facilitate teachers in sharing material, assignments and conducting examinations. And can facilitate students in obtaining material, collecting assignments and doing exam questions. The design of this system is made using the PHP programming language, MySQL database and usecase diagrams. The results of testing the system using the blackbox method involved 8 respondents and the results showed that the system built was in accordance with user requirements and could run very well.